EFEKTIVITAS KENTHONGAN BANYUMAS SEBAGAI MEDIA PEMBELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Dwiyanti, Aris Naeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science learning in elementary schools often faces challenges such as low student engagement and the inadequate use of local wisdom as a learning resource. However, integrating local culture into learning has the potential to improve conceptual understanding and foster student interest in learning. This study aims to determine the effectiveness of using local wisdom-based learning media, such as the Banyumas kenthongan, on improving fifth-grade elementary school students' science learning outcomes. This study used a quantitative approach with a quasi-experimental method and a one-group pretest-posttest design. The subjects consisted of 16 fifth-grade students. Data were collected through pretest and posttest learning achievement tests, then analyzed using a one-tailed t-test and N-gain analysis. The results showed that the average posttest score was higher than the average pretest score. The one-tailed t-test yielded a calculated t-value of 1.77, which is greater than the t-table value of 1.753, indicating statistically significant improvement in learning outcomes. Furthermore, the N-gain analysis yielded a score of 0.7, which falls into the moderate category. These findings indicate that the use of Banyumas kenthongan media is effective in improving fifth-grade elementary school students' science learning outcomes and supporting local wisdom-based learning.